2011
DOI: 10.1128/cvi.05292-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Ehrlichia P28 Outer Membrane Proteins Confers Protection in a Mouse Model of Ehrlichiosis

Abstract: The obligately intracellular bacterium Ehrlichia chaffeensis that resides in mononuclear phagocytes is the etiologic agent of human monocytotropic ehrlichiosis (HME). HME is an emerging and often life-threatening, tick-transmitted infectious disease in the United States. Effective primary immune responses against Ehrlichia infection involve generation of Ehrlichia-specific gamma interferon (IFN-␥)-producing CD4 ؉ T cells and cytotoxic CD8؉ T cells, activation of macrophages by IFN-␥, and production of Ehrlichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Immunization of mice with recombinant P28, which functions as a porin [22], protects mice from E. chaffeensis challenge [21]. Additionally, in a mouse model of HME, immunization of mice with Ehrlichia muris P28 conferred protection from E. muris challenge [25]. As another control, to rule out the possibility that inhibition of binding is a general property of antibody neutralization of any E. chaffeensis cell surface proteins, we examined whether antibody against P28 blocks E. chaffeensis binding and entry.…”
Section: Resultsmentioning
confidence: 99%
“…Immunization of mice with recombinant P28, which functions as a porin [22], protects mice from E. chaffeensis challenge [21]. Additionally, in a mouse model of HME, immunization of mice with Ehrlichia muris P28 conferred protection from E. muris challenge [25]. As another control, to rule out the possibility that inhibition of binding is a general property of antibody neutralization of any E. chaffeensis cell surface proteins, we examined whether antibody against P28 blocks E. chaffeensis binding and entry.…”
Section: Resultsmentioning
confidence: 99%
“…A DNA vaccine targeting a p28 outer membrane protein homolog (MAP1) in another Ehrlichia species, E. ruminantium, also confers partial protection against infection challenges (16). Similarly, recent studies described that p28 outer membrane proteins of E. muris stimulate mouse memory B and T cell responses, reducing the bacterial burden after 10 to 14 days postchallenge with wild-type infection (17,18). Several studies of Ehrlichia species also demonstrated that attenuated strains offer a high level of protection.…”
mentioning
confidence: 99%
“…Antigen-specific CD4 C Th1 cells and CD8 C Tcl cells are well known to play key effector functions in the control of intracellular bacterial infection. 25 Antigen-specific CD8 C Tcl cells are critical for the clearance of intracellular bacteria. 26 During Toxoplasma gondii infections, IFN-g-producing CD8 C T cells are the major effectors, and IFN-g-producing CD4 C T cells play a synergistic role in protection against this pathogen.…”
Section: Discussionmentioning
confidence: 99%